Does Biochar Alleviate Salt Stress Impact on Growth of Salt-Sensitive Crop Common Bean - Karabay, Ufkay; Toptas, Asli; Yanik, Jale; Aktas, Lale (Communications in Soil Science and Plant Analysis, 2021)
This study aimed to evaluate the role of biochar properties and application rate in the alleviation of negative impacts of salinity stress on the growth of salt-sensitive common bean (Phaseolus vulgaris L.). The biochar was obtained by slow pyrolysis of olive pruning at 400°C and characterized as high alkaline (9.3) and having a high cation exchange capacity (CEC) and low electrical conductivity (EC) with high porous surface morphology. Plants were grown in the greenhouse and subjected to different amounts of salt (0, 25, 50 mM NaCl) and biochar rate (0, 5, 15 t/ha). Salinity stress reduced shoot growth, biomass accumulation, total chlorophyll and carotenoid content, these parameters were ameliorated by biochar. Adverse effects of salinity on pod settings were also mitigated by biochar supplements. Salinity triggered oxidative stress monitored by increasing hydrogen peroxide (H 2 O 2 ) content and cell membrane permeability of leaves were mitigated by only 5 t/ha biochar application in contrast 15 t/ha biochar extended oxidative stress level. Our results showed that biochar application may be a promising strategy to increase common bean growth under saline soils due to its specific physicochemical properties, particularly high Na + adsorption capacity. However, the higher biochar application rate may augment the adverse effects of soil salinity for salt-sensitive bean growth due to its contribution to the cumulative EC level of the soil.